Determination of yields and agricultural characters of some perennial forage grasses under Samsun (Turkey) ecological conditions - Acar Z.; Ayan I.; Basaran U.; Mut H.; Onal Asci O. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
This study was carried out under Samsun ecological conditions in 2005-2006 in order to determine some agricultural and morphological characters of four ryegrass, orchard grass and timothy cultivars. Main stem lengths of ryegrass, orchard grass and timothy cultivars were between 69.90-77.20 cm, 97.60-105.90 cm, 71.90-99.00 cm, respectively; dry matter yield for the same cultivars were between 3420.7-3860.7, 4560.6-4970.9, 5280.6-6180.3 kg/ha, respectively.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)